The Effect of News Announcements on the Volatility of Share Prices of PT. Bank Syariah Indonesia Tbk - Sofia; Mediaty; Alamsyah, Muhammad Fajar; Asri, Wenny Nadya; Intani, Fitria; Jumadi, Sri Wahyuni; Habbe, Abdul Hamid (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study analyzes the effect of news announcement on stock price volatility of PT Bank Syariah Indonesia Tbk (BSI). Using a quantitative approach, historical data of BSI stock prices and relevant news announcements were collected for the study period. Through regression analysis, this study found a significant influence between news announcements and BSI stock price volatility. News announcements containing important information about a company's performance or management changes can lead to significant stock price fluctuations. These results provide insights for investors and market participants in managing risks and making appropriate investment decisions. The practical implication is the importance of paying attention to recent news announcements for risk management. Further studies could involve other factors that affect BSI's share price volatility and look at the long-term impact of news announcements on overall company performance.